Apparent Skin Discoloration about the Knee Joint: A Rare Sequela of Metallosis after Total Knee Replacement. (24th March 2015) - Jayasekera, Narlaka; Gouk, Conor; Patel, Amit; Eyres, Keith
Abstract : Introduction . Metallosis is a phenomenon most commonly associated with hip replacement. However it can occur in any metallic implant subject to wear. Wear creates metal debris, which is deposited in the surrounding soft tissue. This leads to many local adverse reactions including, but not limited to, implant loosening/osteolysis, pain, and effusion. In the deeper joints, for example, the hip, metal deposits are mostly only seen intraoperatively. Case Study . A 74-year-old lady represented to orthopaedic outpatient clinic. Her principle complaint was skin discolouration, associated with pain and swelling over the left knee, on the background of a previous total knee replacement with a metal backed patella resurfacing six years. A plain radiograph revealed loosening of the patellar prosthesis. A diagnosis of metallosis was made; the patient underwent debridement of the stained soft tissue and primary revision of the prosthesis. She remained symptom-free five years after revision. Discussion . Metallosis results in metallic debris which causes tissue staining, often hidden within the soft tissue envelope of the hip, but more apparent in the knee. Metallosis may cause pain, effusion, and systemic symptoms because of raised levels of serum-metal ions. Surgical intervention with revision and debridement can have good functional results.